FROM LOGIS GATE TO VERILOGCODE A HANDBOOK GUIDE - HASSAN , HASLIZA (2024)
"From Logic Gate to Verilog Code: A Handbook Guide" is an essential resource for anyone interested in understanding the fundamentals of digital design and programming using Verilog. This comprehensive handbook takes readers on a journey from the basics of logic gates and digital circuits to advanced Verilog coding techniques, making it accessible to beginners while also providing valuable insights for experienced engineers.The book begins by introducing the foundational concepts of digital logic, including Boolean algebra, logic gates, and basic circuit design principles. It then progresses to explain the role of Verilog in digital design and covers topics such as module instantiation, data types, operators, and behavioural modelling.One of the key strengths of this handbook is its hands- on approach. Each chapter is accompanied by practical examples and exercises that allow readers to apply their knowledge and reinforce their understanding of Verilog coding. The book also includes step-by-step guides for designing common digital circuits and implementing them in Verilog, making it a valuable reference for both learning and practical application.